2018
DOI: 10.1080/09297049.2018.1470611
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic learning in children with isolated and combined reading and spelling deficits

Abstract: Dissociations between reading and spelling problems are likely to be associated with different underlying cognitive deficits, and with different deficits in orthographic learning. In order to understand these differences, the current study examined orthographic learning using a printed-word learning paradigm. Children (4th grade) with isolated reading, isolated spelling and combined reading and spelling problems were compared to children with age appropriate reading and spelling skills on their performance dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recent evidence on the partial dissociability between reading and spelling deficits also points to the mediating role of the speed component in reading ( Mehlhase et al, 2019 ). Thus, spelling deficits were associated to deficient storing of orthographic representations in long-term memory while isolated reading fluency deficits were associated to spared orthographic representations but slowed access to these representations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence on the partial dissociability between reading and spelling deficits also points to the mediating role of the speed component in reading ( Mehlhase et al, 2019 ). Thus, spelling deficits were associated to deficient storing of orthographic representations in long-term memory while isolated reading fluency deficits were associated to spared orthographic representations but slowed access to these representations.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results are thus more consistent with the partial cue than the over-reliance hypothesis, although the lack of a clear decoding deficit in SpD is not completely in line with the former either. Recent evidence from an orthographic learning study (Mehlhase et al, 2019) suggests that SpD children have problems in developing and storing stable orthographic representations in long-term memory. This finding represents a likely alternative explanation for orthographic weaknesses observed in SpD, but needs further replication.…”
Section: Spd Groupmentioning
confidence: 99%
“…As literacy development progresses, the acquisition of orthographic knowledge becomes pivotal for both spelling and reading. Based on findings in an orthographic learning experiment, Mehlhase et al (2019) suggested that dissociations might occur as a consequence of distinct orthographic deficits. Isolated reading disorder is characterized by a deficiency in efficiently processing stored words despite a lack of deficit in storing orthographic representations.…”
Section: Introductionmentioning
confidence: 99%